Grammatical features of ancient Chinese pronoun (Journal of Oriental Studies, 2016)
In this article complete description is given pronoun of ancient chinese language, examined their grammatical features in ancient and modern Chinese and importance is in the modern process of study of language.
Keywords: ancient Chinese language; grammar; pronoun; language learning process